Preparation method and coating process of fireproof coating for cabinet door
By using a cross-linked network of modified ammonium polyphosphate and expandable graphite, the problems of flame retardancy efficiency and adhesion of traditional fire-retardant coatings for wooden cabinet doors have been solved, achieving high strength, wear resistance and stable fire resistance performance, thus improving fire safety and durability.
Patent Information
- Application Number
- CN202511200370.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-12-02
AI Technical Summary
Traditional fire-retardant coatings for wooden cabinet doors suffer from insufficient flame retardancy, poor adhesion, and durability defects. They are prone to cracking and peeling, especially in high-temperature and high-humidity environments, making it difficult to meet high fire resistance requirements.
By using materials such as modified ammonium polyphosphate, expandable graphite, thiocarbamate and siloxane, a multi-layer cross-linked network is formed through mercapto-olefin click reaction, which enhances the flame retardant properties and adhesion of the coating and builds a highly efficient fire barrier.
It achieves high strength, wear resistance and stable fire resistance, improves the fire safety and durability of wooden cabinet doors, and reaches an ultra-high fire resistance limit of 85 minutes and a top oxygen index of 43.8%.
Smart Images

Figure CN121045894A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fire-retardant coating production technology, and in particular to a method for preparing and coating a fire-retardant coating for cabinet doors. Background Technology
[0002] As a core component of building interior decoration, the fire safety of wooden cabinet doors is directly related to the safety of life and property. While traditional fire-retardant coatings for wooden cabinet doors possess some flame-retardant properties, they suffer from weak adhesion, insufficient weather resistance, and are prone to cracking and peeling, especially in high-temperature and high-humidity environments, leading to the failure of the flame-retardant layer. Furthermore, existing fire-retardant coatings often face technical bottlenecks due to film-forming properties and compatibility issues with flame-retardants, resulting in low strength of the expanded char layer and rapid decay of flame-retardant efficiency.
[0003] Traditional fire-retardant coatings face the following bottlenecks when applied to wood-based substrates:
[0004] Insufficient flame retardant efficiency: Ordinary intumescent coatings rely on a single ammonium polyphosphate (APP) / pentaerythritol system, which has a low expansion ratio at high temperatures, and the char layer is loose and prone to collapse, making it difficult to meet the fire resistance limit requirements of high fire-resistant cabinets.
[0005] Poor adhesion to the substrate: Wood substrates are porous and hydrophobic, and coatings are prone to stress cracks due to thermal cycling, resulting in decreased adhesion.
[0006] Durability defects: Organic resin matrix has poor thermal stability and is prone to decomposition and carbon loss at high temperatures; inorganic coatings, although heat-resistant, have poor flexibility, are prone to powdering when mechanically sanded, and have poor abrasion resistance.
[0007] In conclusion, there is an urgent need to develop a fire-retardant coating with high flame retardancy, high adhesion, and strong durability. Summary of the Invention
[0008] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing fire-retardant coatings for cabinet doors and a coating process.
[0009] To achieve the above objectives, the present invention adopts the following technical solution:
[0010] This invention first proposes a method for preparing a fire-retardant coating for cabinet doors, comprising the following steps:
[0011] S1, Flame retardant pre-modification
[0012] Ammonium polyphosphate powder was added to a reaction vessel, ethylenediamine aqueous solution was sprayed, the mixture was stirred at 60°C for 2 hours, filtered, and dried at 80°C to obtain modified APP.
[0013] Expandable graphite was mixed with KH-550 ethanol solution and reacted at 80°C for 3 hours. After centrifugation, modified EG was obtained and dried at 60°C for later use.
[0014] The primary amine group of ethylenediamine undergoes a nucleophilic substitution reaction with the phosphate group at the end of the ammonium polyphosphate (APP) molecular chain to form a P-NH-CH2-CH2-NH2 structure. The silanol (Si-OH) generated by the hydrolysis of KH-550 (γ-aminopropyltriethoxysilane) undergoes a condensation reaction with the hydroxyl group (-OH) on the surface of expandable graphite (EG) to form a Si-OC covalent bond.
[0015] S2, preparation of triazine trithiol solution
[0016] Dipropylene glycol methyl ether was added to triazine trithiol and stirred in a water bath at 40°C for 30 minutes until the triazine trithiol was completely dissolved. Antioxidant 1010 was added to obtain a triazine trithiol solution. The solution was then transferred to a sealed container and protected with nitrogen gas until it was ready for use.
[0017] S3, Prepolymer Synthesis
[0018] At 65℃±1℃, triazine trithiol solution was added to the reactor, and hexamethylene diisocyanate was slowly added dropwise while stirring at 120 rpm. The reaction was maintained at this temperature for 2.5 h. The temperature was then lowered to 50℃, dibutyltin dilaurate was added, and the reaction was continued for 1 h. Anhydrous acetone was added for dilution to obtain the prepolymer.
[0019]
[0020] At room temperature, sodium dodecyl sulfate, deionized water, defoamer, and modified EG were mixed to prepare a premix, and the pH was adjusted to 4 using 0.05 mol / L sodium acetate / acetic acid.
[0021] The prepolymer was injected into the premixed liquid and emulsified at high speed of 5000 rpm for 15 min to obtain the preemulsion.
[0022] After emulsification, acetone was removed and recovered by stepwise heating. The mixture was stirred at 200 rpm for 30 min at 50 °C, stirred at 200 rpm for 20 min at 65 °C, and then dehydrated under vacuum at -0.09 MPa to obtain a polythiourethane emulsion.
[0023] Add acrylic emulsion, modified APP, polyether-modified siloxane, cation exchange resin, and vinyltriethoxysilane to a stainless steel reactor with a Teflon coating. Preheat the reactor to 80°C by stirring at 300 rpm. Slowly add polythiourethane emulsion and stir at 1200 rpm for 30 min. Add hydrophobic agent, bactericide, and defoamer at 800 rpm and continue the reaction for 15 min.
[0024] The ethoxy group of VTES is partially hydrolyzed to silanol-Si(OH)3:
[0025]
[0026] After preparing a 10% solids-content aqueous solution of thickener, it was slowly added to the reactor and stirred at 200 rpm for 10 min. The viscosity was adjusted to 80-100 s at Fort-4 cup. Defoamer and azobisisobutyronitrile were added, along with deionized water. The solids content of the system was adjusted to 50%. The mixture was defoamed at -0.06 MPa and 400 rpm for 10 min. The mixture was then filtered through a 200-mesh sieve to obtain a fire-retardant coating for cabinet doors.
[0027]
[0028] Preferably, in S1, the ethylenediamine aqueous solution is a 10% ethylenediamine aqueous solution, and the amount used is equal to the mass of the ammonium polyphosphate powder; the KH-550 ethanol solution is a 12% KH-550 ethanol solution, and the amount used is 3% of the mass of the expandable graphite.
[0029] Preferably, in step S2, the amount of antioxidant 1010 is 0.5% of the mass of triazine trithiol.
[0030] Preferably, in S3, the ratio of mercapto groups to isocyanate groups in triazine trithiol and hexamethylene diisocyanate is 1:0.33-0.38; the mass of dibutyltin dilaurate is 0.2% of the mass of the prepolymer; and the mass of anhydrous acetone is 10% of the reactant mass of the prepolymer.
[0031] Preferably, in step S4, the mass of sodium dodecyl sulfate is 0.3% of the premix; the mass ratio of defoamer to modified EG is 12:0.3; the mass of polyether-modified siloxane is 0.2% of the acrylic emulsion; the mass of cation exchange resin is 2% of the mixed emulsion; the hydrophobic agent is an alkyl / fluoroalkyl-modified organosilicon hydrophobic agent; the defoamer is a polyether siloxane defoamer; the bactericide is an isothiazolinone bactericide; and the solid content of the waterborne acrylic resin emulsion is 45±2%, p H = 7.5-8.5; the mass ratio of waterborne acrylic resin emulsion, vinyltriethoxysilane, modified APP, polythiourethane emulsion, hydrophobic agent, bactericide, and defoamer is 45-55:1.2-1.6:18:9.5-9:0.8:0.3:0.1; 85%-90% of dipropylene glycol methyl ether is recovered from the pre-emulsion solution by vacuum distillation supplemented by rectification and vacuum dehydration, and the remaining dipropylene glycol methyl ether will remain in the coating as a film-forming aid.
[0032] Preferably, in step S5, the thickener is a hydrophobically modified polyurethane thickener, and the amount used is 0.1% of the total mass of the reactants; the mass of azobisisobutyronitrile is 0.1% of the total mass of the reactants; the mass of the defoamer added for the second time is 0.05% of the total mass of the system; and the cationic resin is recovered after filtration.
[0033] This invention also proposes a coating process for the fire-retardant coating for cabinet doors prepared using the aforementioned method, comprising the following steps:
[0034] (I) Substrate Pretreatment
[0035] The wooden cabinet doors are mechanically sanded with 240# sandpaper to remove burrs, and the roughness Ra is ≤ 3.2μm. Then, they are dusted with compressed air.
[0036] Spray a water-based epoxy sealing primer with a wet film thickness of 30μm, pre-bake at 70℃ for 3min with infrared, and the dry film thickness is 15±2μm.
[0037] (II) Fire-retardant coating application
[0038] Airless spraying was used to coat the cabinet doors, and the spraying parameters were set as follows:
[0039] Nozzle orifice diameter 0.5mm, spraying pressure 12-14MPa, spray gun distance 25-30cm, gun travel speed 0.8-1.0m / s, spraying angle ±10° perpendicular to cabinet door;
[0040] The first spraying was carried out at 25℃, with a wet film thickness of 120μm and a coverage of over 95%.
[0041] Pre-dry the surface coating at 70℃ for 3 minutes using infrared pre-baking;
[0042] The second wet film coating is 150μm thick, with the corners thickened to 180μm.
[0043] (III) Drying and Curing
[0044] Curing was performed using an infrared tunnel oven with hot air at 60℃ for 30 minutes, with a set wind speed of 8m / s and an air exchange rate of 20 times / hour; the conveyor belt speed was 1.2m / min; after grinding the edge burrs with an angle grinder, the cabinet was placed at 25℃ for 24 hours to obtain a cabinet door coated with fire-retardant paint.
[0045] During the hot air curing stage, a mercapto-olefin click reaction occurs between thiols (R-SH) and vinyl groups (C=C) in the coating:
[0046]
[0047] This further cross-links the coating system, improving the coating's wear resistance.
[0048] Preferably, the water-based epoxy sealing primer is a water-based acrylic wood sealing primer.
[0049] Compared with the prior art, the beneficial effects of the present invention are:
[0050] This invention constructs a multi-layer flame-retardant system, which significantly improves fire resistance compared to traditional fire-retardant coatings:
[0051] When exposed to high temperatures, the modified ammonium polyphosphate decomposes to produce ammonia (NH3) and water vapor (H2O), diluting the concentration of combustible gases and oxygen. At the same time, it generates polyphosphate to catalyze the dehydration of the cabinet door matrix into carbon. In addition, the thiocarbamate structure (-NH-C(=S)-) in the coating decomposes at high temperatures to release sulfur-containing free radicals (such as ·SO2, ·HSO2), which capture highly active free radicals (·H, ·OH) during the combustion process and interrupt the chain combustion reaction.
[0052] At 150-300℃, the modified APP inserted between the layers vaporizes, and the modified EG sheets expand rapidly along the arrangement direction of the modified APP, forming a worm-like expanded carbon layer with excellent heat insulation and oxygen barrier properties, and capable of blocking molten droplets; the cabinet door substrate dehydrates into carbon, which combines with the carbon layer of expanded graphite to form a denser and more stable "graphite-phosphorus carbon" composite expanded carbon layer.
[0053] Triazine trithiol reacts with hexamethylene diisocyanate to form a highly cross-linked polythiourethane network. This structure itself exhibits high thermal stability and char residue, providing initial skeletal support for the coating. During curing, vinyltriethoxysilane undergoes hydrolysis and condensation to form a Si-O-Si inorganic network, improving the coating's heat resistance. Furthermore, the vinyl group (-CH=CH2) undergoes a "thiol-ene click reaction" with the thiol (-SH), covalently bonding the siloxane network to the organic polymer network, significantly enhancing the coating's integrity, adhesion, and high-temperature stability.
[0054] This invention uses a mercapto-olefin click reaction to connect an acrylic resin matrix with a polythiourethane network, further improving the crosslinking degree of the coating. Compared with traditional coatings, the system has stronger stability and higher adhesion.
[0055] The polythiourethane backbone constructed in this invention is a high-strength organic three-dimensional cross-linked network that strongly resists external extrusion deformation. It serves as the skeleton support and ensures the wear resistance of the coating. In addition, the siloxane changes the traditional coating where flame retardants rely on physical adsorption, and instead relies on chemical bonding, which can eliminate weak interface layers, uniformly disperse wear stress, and further improve the wear resistance of the coating.
[0056] In summary, this invention constructs an efficient, stable, and high-strength fire barrier on the surface of a wooden cabinet door through multiple synergistic mechanisms, including gas-phase free radical quenching, expansion physical isolation, catalytic carbonization reinforcement, high cross-linking network providing system stability, siloxane-enhanced modified EG expanded carbon layer, and the interfacial strength between the high cross-linking network and the cabinet door matrix. This achieves an ultra-long fire resistance limit and excellent comprehensive performance. Attached Figure Description
[0057] Figure 1The 1H NMR spectrum of the polythiourethane obtained in this invention is shown below. Detailed Implementation
[0058] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0059] The purity and manufacturers of the various drugs used in the experiment are shown in Table 1.
[0060] Table 1. Raw Material Drug Information
[0061] drug Specification Manufacturer Ammonium polyphosphate Industrial grade Hubei Xinkang Pharmaceutical & Chemical Co., Ltd. Expandable graphite Industrial grade Sigma Aldrich (Shanghai) Trading Co., Ltd. KH-550 Industrial grade Shandong Fengpan New Materials Co., Ltd. Triazine trithiol Industrial grade Henan Evonik Biotechnology Co., Ltd. Dipropylene glycol methyl ether Industrial grade Jinan Yuanshang New Materials Co., Ltd. Antioxidant 1010 Industrial grade Shandong Xinheng Chemical Co., Ltd. Hexamethylene diisocyanate Industrial grade Jinan Zhiyuancheng Chemical Co., Ltd. Vinyltriethoxysilane Industrial grade Shandong Xiya Chemical Co., Ltd. Sodium dodecyl sulfate Industrial grade Qingdao Port Liwei Import & Export Co., Ltd. Anhydrous acetone Industrial grade Shanghai Runjie Chemical Reagent Co., Ltd. acrylic emulsion Industrial grade Nantong Runfeng Petrochemical Co., Ltd. Polyether modified siloxane Industrial grade Hubei Zhonglong Kangcheng Fine Chemical Co., Ltd. Cation exchange resin Industrial grade Shandong Xiya Chemical Co., Ltd. Alkyl / fluoroalkyl modified organosilicon hydrophobic agents Industrial grade Shandong Hemiao New Materials Co., Ltd. Polyether siloxane defoamer Industrial grade Yixing Jiangshan Biotechnology Co., Ltd. Isothiazolinone fungicides Industrial grade Foshan Liyuan Chemical Co., Ltd. Hydrophobic modified polyurethane thickener Industrial grade Hubei Zhonglong Kangcheng Fine Chemical Co., Ltd. Waterborne epoxy sealing primer Industrial grade Hebei Chenyang Industry and Trade Group Co., Ltd.
[0062] Example 1:
[0063] S1, Flame retardant pre-modification
[0064] Ammonium polyphosphate powder was added to a reaction vessel, ethylenediamine aqueous solution was sprayed, the mixture was stirred at 60°C for 2 hours, filtered, and dried at 80°C to obtain modified APP.
[0065] Expandable graphite was mixed with KH-550 ethanol solution and reacted at 80°C for 3 hours. After centrifugation, modified EG was obtained and dried at 60°C for later use.
[0066] S2, preparation of triazine trithiol solution
[0067] Dipropylene glycol methyl ether was added to triazine trithiol and stirred in a water bath at 40°C for 30 minutes until the triazine trithiol was completely dissolved. Antioxidant 1010 was added to obtain a triazine trithiol solution. The solution was then transferred to a sealed container and protected with nitrogen gas until it was ready for use.
[0068] S3, Prepolymer Synthesis
[0069] At 65℃±1℃, triazine trithiol solution was added to the reactor, and hexamethylene diisocyanate was slowly added dropwise while stirring at 120 rpm. The reaction was maintained at this temperature for 2.5 h. The temperature was then lowered to 50℃, dibutyltin dilaurate was added, and the reaction was continued for 1 h. Anhydrous acetone was added for dilution to obtain the prepolymer.
[0070] S4, Coating Emulsification
[0071] At room temperature, sodium dodecyl sulfate, deionized water, defoamer, and modified EG were mixed to prepare a premix, and the pH was adjusted to 4 using 0.05 mol / L sodium acetate / acetic acid.
[0072] The prepolymer was injected into the premixed liquid and emulsified at high speed of 5000 rpm for 15 min to obtain a polythiourethane preemulsion.
[0073] After emulsification, acetone was removed and recovered by stepwise heating. The mixture was stirred at 200 rpm for 30 min at 50 °C, stirred at 200 rpm for 20 min at 65 °C, and then dehydrated under vacuum at -0.09 MPa to obtain a mixed emulsion.
[0074] Add acrylic emulsion, modified APP, polyether-modified siloxane, cation exchange resin, and vinyltriethoxysilane to a stainless steel reactor with a Teflon coating. Stir at 300 rpm and preheat to 80°C. Slowly add polythiourethane pre-emulsion and stir at 1200 rpm for 30 min. Add hydrophobic agent, bactericide, and defoamer at 800 rpm and continue the reaction for 15 min.
[0075] S5, Coating System Adjustment
[0076] After preparing a 10% solids-content aqueous solution of thickener, it was slowly added to the reactor and stirred at 200 rpm for 10 min. The viscosity was adjusted to 80-100 s at Fort-4 cup. Defoamer and azobisisobutyronitrile were added, along with deionized water. The solids content of the system was adjusted to 50%. The mixture was defoamed at -0.06 MPa and 400 rpm for 10 min. The mixture was then filtered through a 200-mesh sieve to obtain a fire-retardant coating for cabinet doors.
[0077] The mass ratio of ammonium polyphosphate powder to ethylenediamine is 10:1; the amount of KH-550 is 3% of the mass of expandable graphite; and the amount of antioxidant 1010 is 0.5% of the mass of triazine trithiol.
[0078] The ethylenediamine aqueous solution is a 10% aqueous solution of ethylenediamine at a mass ratio of 10:1 to ammonium polyphosphate; the KH-550 ethanol solution is a 12% KH-550 ethanol solution; the mass of the polyether-modified siloxane is 0.2% of the acrylic emulsion; the mass of the cation exchange resin is 2% of the mixed emulsion; the mass of the azobisisobutyronitrile is 0.1% of the total mass of the reactants; the mass of anhydrous acetone is 10% of the prepolymer reactants; the mass of sodium dodecyl sulfate is 0.3% of the premix; the mass of dibutyltin dilaurate is 0.2% of the prepolymer; and the mass of the second added defoamer is 0.05% of the total mass of the system.
[0079] The antioxidant 1010 is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; the hydrophobic agent is an alkyl / fluoroalkyl modified organosilicon hydrophobic agent; the defoamer is a polyether siloxane defoamer; the bactericide is an isothiazolinone bactericide; and the thickener is a hydrophobically modified polyurethane thickener.
[0080] The mass ratio of the triazine trithiol, dipropylene glycol methyl ether, aqueous acrylic resin emulsion, hexamethylene diisocyanate, vinyltriethoxysilane, modified APP, modified EG, hydrophobic agent, defoamer, thickener and bactericide is 5.5:6.6:45:3:1.6:18:12:0.8:0.3:0.9:0.1.
[0081] The aqueous acrylic resin emulsion has a solid content of 44% and a pH of 7.6. 87% of the dipropylene glycol methyl ether is recovered from the pre-emulsion solution by vacuum distillation supplemented by rectification and vacuum dehydration. The remaining dipropylene glycol methyl ether will remain in the coating as a film-forming aid. The cationic resin is recovered after filtration.
[0082] The coating process for the fire-retardant coating on the cabinet door includes the following steps:
[0083] (I) Substrate Pretreatment
[0084] The wooden cabinet doors are mechanically sanded with 240# sandpaper to remove burrs, and the roughness Ra is ≤ 3.2μm. Then, they are dusted with compressed air.
[0085] Spray a 30μm wet film thickness water-based epoxy sealing primer and pre-bake at 70℃ for 3 minutes using infrared technology.
[0086] Dry film thickness 15±2μm;
[0087] (II) Fire-retardant coating application
[0088] Airless spraying was used to coat the cabinet doors, and the spraying parameters were set as follows:
[0089] Nozzle orifice diameter 0.5mm, spraying pressure 12-14MPa, spray gun distance 25-30cm, gun travel speed 0.8-1.0m / s, spraying angle ±10° perpendicular to cabinet door;
[0090] The first spraying was carried out at 25℃, with a wet film thickness of 120μm and a coverage of over 95%.
[0091] Pre-dry the surface coating at 70℃ for 3 minutes using infrared pre-baking;
[0092] The second wet film coating is 150μm thick, with the corners thickened to 180μm.
[0093] (III) Drying and Curing
[0094] Curing was performed using an infrared tunnel oven with hot air at 60℃ for 30 minutes, with a set wind speed of 8m / s and an air exchange rate of 20 times / hour; the conveyor belt speed was 1.2m / min; after grinding the edge burrs with an angle grinder, the cabinet was placed at 25℃ for 24 hours to obtain a cabinet door coated with fire-retardant paint.
[0095] The prepolymer was separated and purified to obtain the product of the reaction between triazine trithiol and hexamethylene diisocyanate, a highly cross-linked polythiourethane polymer. This polymer was characterized by 1H NMR spectroscopy. Figure 1 ;
[0096] The protons on the triazine ring are highly deshielded due to the strong electron-withdrawing effect, resulting in a sharp singlet (s) at high fields (>8.0 ppm). The secondary amine group (-NH-) generated in the reaction exhibits a broad, blunt peak at 5.5-6.5 ppm due to hydrogen bonding and the influence of the thiocarbonyl group (C=S). The methylene chain of HDI (-(CH2)6-) splits into complex multiplets in the low field region. At the grafting site of vinyltriethoxysilane (VTES), the vinyl proton (=CH2) is at 5.6-6.0 ppm (dd), =CH- at 6.2 ppm (m), and the -O-CH2-CH3 proton is at 1.1-1.3 ppm (t, 3H) and 3.7-3.9 ppm (q, 2H). The ethoxy protons exhibit characteristic triplets (-CH3) and quartets (-O-CH2-).
[0097] Example 2:
[0098] The fire-retardant coating of Example 2 is prepared in the same way as that of Example 1, but the mass ratio of the triazine trithiol, dipropylene glycol methyl ether, waterborne acrylic resin emulsion, hexamethylene diisocyanate, vinyltriethoxysilane, modified APP, modified EG, hydrophobic agent, defoamer, thickener and bactericide is 5.5:6.8:50:2.8:1.4:18:12:0.8:0.3:0.9:0.1.
[0099] The aqueous acrylic resin emulsion has a solid content of 47% and a pH of 8.1. 85% of the dipropylene glycol methyl ether is recovered from the pre-emulsion solution by vacuum distillation supplemented by rectification and vacuum dehydration. The remaining dipropylene glycol methyl ether will remain in the coating as a film-forming aid.
[0100] The coating process for the fire-retardant coating on the cabinet door is the same as in Example 1.
[0101] Example 3:
[0102] The fire-retardant coating of Example 3 is prepared in the same way as that of Example 1, but the mass ratio of the triazine trithiol, dipropylene glycol methyl ether, waterborne acrylic resin emulsion, hexamethylene diisocyanate, vinyltriethoxysilane, modified APP, modified EG, hydrophobic agent, defoamer, thickener and bactericide is 5.5:7.0:55:2.6:1.2:18:12:0.8:0.3:0.9:0.1.
[0103] The aqueous acrylic resin emulsion has a solid content of 46% and a pH of 8.0. 89% of the dipropylene glycol methyl ether is recovered from the pre-emulsion solution by vacuum distillation supplemented by rectification and vacuum dehydration. The remaining dipropylene glycol methyl ether will remain in the coating as a film-forming aid.
[0104] The coating process for the fire-retardant coating on the cabinet door is the same as in Example 1.
[0105] Based on this, the following design was also created:
[0106] Comparative Example 1: Same formulation and experimental method as Example 2, but with insufficient addition of dipropylene glycol methyl ether;
[0107] Comparative Example 2: The formulation and experimental method were the same as in Example 2, but an excess of dipropylene glycol methyl ether was added;
[0108] Comparative Example 3: Same formulation and experimental method as Example 2, but with insufficient addition of aqueous acrylic resin emulsion;
[0109] Comparative Example 4: The formulation and experimental method were the same as in Example 2, but an excess of aqueous acrylic resin emulsion was added;
[0110] Comparative Example 5: Same formulation and experimental method as Example 2, but with insufficient addition of hexamethylene diisocyanate;
[0111] Comparative Example 6: Same formulation and experimental method as Example 2, but with the addition of excess hexamethylene diisocyanate;
[0112] Comparative Example 7: Same formulation and experimental method as Example 2, but with insufficient addition of vinyltriethoxysilane;
[0113] Comparative Example 8: Same formulation and experimental method as Example 2, but with the addition of excess vinyltriethoxysilane;
[0114] The specific formula is shown in Table 2:
[0115] Table 2. Formulation of a fire-retardant coating for cabinet doors
[0116]
[0117] The fire-retardant coating of the present invention was tested for fire resistance limit, oxygen index (LOI), adhesion, resistance to thermal cycling, and abrasion resistance according to standards GB / T 9978.1-2019, GB / T 2406.2-2009, GB / T 9286-2021, GB / T 31543-2015, and GB / T 1768-2006. The corresponding results are shown in Table 3.
[0118] Table 3. Test data of various performance characteristics of fire-retardant coatings
[0119]
[0120] Data analysis shows that:
[0121] By comparing Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that insufficient dosage of dipropylene glycol methyl ether as a solvent / film-forming aid (i.e., in Comparative Example 1) leads to uneven component dispersion, making it difficult for the coating to form a dense film. Macroscopically, this manifests as a decrease in adhesion from grade 0 to grade 1, along with the appearance of microcracks during thermal cycling tests and a deterioration in abrasion resistance. Excessive dosage (i.e., in Comparative Example 2) disrupts the stability of the emulsion system, causing the coating to easily peel off during testing, significantly reducing the fire resistance limit (the core fire-retardant performance), and also worsening abrasion resistance. Therefore, the dosage of dipropylene glycol methyl ether needs to be precisely controlled to balance dissolution and dispersion, film-forming properties, and emulsion stability.
[0122] Comparative Examples 1, 3, and 4 show that for waterborne acrylic resin emulsions used as the matrix resin, the waterborne acrylic resin is the film-forming matrix of the coating, providing a continuous phase for the coating system and encapsulating the flame-retardant filler. When insufficient, other components will be exposed, the adhesion will drop to level 2, and the fire resistance limit will drop from 85 min to 34. When excessive, the effective components will be diluted, and all the properties of the fire-retardant coating will decrease significantly.
[0123] By comparing Example 1, Comparative Example 5, and Comparative Example 6, it can be seen that for hexamethylene diisocyanate as a crosslinking agent, the -NCO and -SH groups of hexamethylene diisocyanate react quantitatively to avoid insufficient crosslinking leading to insufficient strength of the polythiourethane network, or over-crosslinking, which causes the polythiourethane to change from mercapto groups to isocyanate groups, occupying the reaction sites of vinyltriethoxysilane and triazine trithiol, resulting in a significant decrease in both wear resistance and adhesion.
[0124] By comparing Example 1, Comparative Example 7, and Comparative Example 8, it can be seen that for vinyltriethoxysilane as a coupling agent, vinyltriethoxysilane forms a double bond system of Si-O-lignocellulose and CS-polymer in the coating system through hydrolysis condensation and mercapto click reaction, which greatly improves the adhesion of the coating. Therefore, when the amount of vinyltriethoxysilane added is insufficient, the crosslinking degree between the polythiourethane network and the acrylic resin is insufficient. When the amount of vinyltriethoxysilane added is excessive, the crosslinking density is too high, which will hinder the movement of molecular chains in the coating, reduce elasticity, and result in the worst adhesion among all experimental groups.
[0125] In summary, the fire-retardant coating for cabinet doors of the present invention achieves a comprehensive performance breakthrough through optimized formulation and precision process, including an ultra-high fire resistance limit of 85 min, a top-level oxygen index of 43.8%, grade 0 adhesion, and excellent abrasion resistance of 25 mg, significantly improving the fire safety and durability of wooden cabinet doors.
[0126] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a fire-retardant coating for cabinet doors, characterized in that, Includes the following steps: S1, Flame retardant pre-modification Ammonium polyphosphate powder was added to a reaction vessel, ethylenediamine aqueous solution was sprayed, the mixture was stirred at 60°C for 2 hours, filtered, and dried at 80°C to obtain modified APP. Expandable graphite was mixed with KH-550 ethanol solution and reacted at 80°C for 3 hours. After centrifugation, modified EG was obtained and dried at 60°C for later use. S2, preparation of triazine trithiol solution Dipropylene glycol methyl ether was added to triazine trithiol and stirred in a water bath at 40°C for 30 minutes until the triazine trithiol was completely dissolved. Antioxidant 1010 was added to obtain a triazine trithiol solution. The solution was then transferred to a sealed container and protected with nitrogen gas until it was ready for use. S3, Prepolymer Synthesis At 65℃±1℃, triazine trithiol solution was added to the reactor, and hexamethylene diisocyanate was slowly added dropwise while stirring at 120 rpm. The reaction was maintained at this temperature for 2.5 h. The temperature was then lowered to 50℃, dibutyltin dilaurate was added, and the reaction was continued for 1 h. Anhydrous acetone was added for dilution to obtain the prepolymer. S4, Coating Emulsification At room temperature, sodium dodecyl sulfate, deionized water, defoamer, and modified EG were mixed to prepare a premix, and the pH was adjusted to 4 using 0.05 mol / L sodium acetate / acetic acid. The prepolymer was injected into the premixed liquid and emulsified at high speed of 5000 rpm for 15 min to obtain the preemulsion. After emulsification, acetone was removed and recovered by stepwise heating. The mixture was stirred at 200 rpm for 30 min at 50 °C, stirred at 200 rpm for 20 min at 65 °C, and then dehydrated under vacuum at -0.09 MPa to obtain a polythiourethane emulsion. Add acrylic emulsion, modified APP, polyether-modified siloxane, cation exchange resin, and vinyltriethoxysilane to a stainless steel reactor with a Teflon coating. Preheat the reactor to 80°C by stirring at 300 rpm. Slowly add polythiourethane emulsion and stir at 1200 rpm for 30 min. Add hydrophobic agent, bactericide, and defoamer at 800 rpm and continue the reaction for 15 min. S5, Coating System Adjustment After preparing a 10% solids-content aqueous solution of thickener, it was slowly added to the reactor and stirred at 200 rpm for 10 min. The viscosity was adjusted to 80-100 s at Fort-4 cup. Defoamer and azobisisobutyronitrile were added, along with deionized water. The solids content of the system was adjusted to 50%. The mixture was defoamed at -0.06 MPa and 400 rpm for 10 min. The mixture was then filtered through a 200-mesh sieve to obtain a fire-retardant coating for cabinet doors.
2. The method for preparing a fire-retardant coating for cabinet doors according to claim 1, characterized in that, In S1, the ethylenediamine aqueous solution is a 10% ethylenediamine aqueous solution, and the amount used is equal to the mass of the ammonium polyphosphate powder; the KH-550 ethanol solution is a 12% KH-550 ethanol solution, and the amount used is 3% of the mass of the expandable graphite.
3. The method for preparing a fire-retardant coating for cabinet doors according to claim 1, characterized in that, In S2, the amount of antioxidant 1010 is 0.5% of the mass of triazine trithiol.
4. The method for preparing a fire-retardant coating for cabinet doors according to claim 1, characterized in that, In S3, the ratio of mercapto groups to isocyanate groups in triazine trithiol and hexamethylene diisocyanate is 1:0.33-0.38; the mass of dibutyltin dilaurate is 0.2% of the mass of the prepolymer; and the mass of anhydrous acetone is 10% of the reactant mass of the prepolymer.
5. The method for preparing a fire-retardant coating for cabinet doors according to claim 1, characterized in that, In S4, sodium dodecyl sulfate accounts for 0.3% of the premix; the defoamer and modified EG have a mass ratio of 12:0.3; the polyether-modified siloxane accounts for 0.2% of the acrylic emulsion; the cation exchange resin accounts for 2% of the mixed emulsion; the hydrophobic agent is an alkyl / fluoroalkyl modified organosilicon hydrophobic agent; the defoamer is a polyether siloxane defoamer; the bactericide is an isothiazolinone bactericide; the solid content of the waterborne acrylic resin emulsion is 45±2%, and the pH is _____. 7.5-8.5; The mass ratio of waterborne acrylic resin emulsion, vinyltriethoxysilane, modified APP, polythiourethane emulsion, hydrophobic agent, bactericide, and defoamer is 45-55:1.2-1.6:18:9.5-9:0.8:0.3:0.1; 85%-90% of dipropylene glycol methyl ether is recovered from the pre-emulsion solution by vacuum distillation supplemented by rectification and vacuum dehydration, and the remaining dipropylene glycol methyl ether will remain in the coating as a film-forming aid.
6. The method for preparing a fire-retardant coating for cabinet doors according to claim 1, characterized in that, In step S5, the thickener is a hydrophobically modified polyurethane thickener, and the amount used is 0.1% of the total mass of the reactants; the mass of azobisisobutyronitrile is 0.1% of the total mass of the reactants; the mass of the defoamer added for the second time is 0.05% of the total mass of the system; and the cationic resin is recovered after filtration.
7. The coating process for the fire-retardant coating for cabinet doors prepared using the preparation method according to any one of claims 1-6, characterized in that, Includes the following steps: (I) Substrate Pretreatment The wooden cabinet doors are mechanically sanded with 240# sandpaper to remove burrs, and the roughness Ra is ≤ 3.2μm. Then, they are dusted with compressed air. Spray a water-based epoxy sealing primer with a wet film thickness of 30μm, pre-bake at 70℃ for 3min with infrared, and the dry film thickness is 15±2μm. (II) Fire-retardant coating application Airless spraying was used to coat the cabinet doors, and the spraying parameters were set as follows: Nozzle orifice diameter 0.5mm, spraying pressure 12-14MPa, spray gun distance 25-30cm, gun travel speed 0.8-1.0m / s, spraying angle ±10° perpendicular to cabinet door; The first spraying was carried out at 25℃, with a wet film thickness of 120μm and a coverage of over 95%. Pre-dry the surface coating at 70℃ for 3 minutes using infrared pre-baking; The second wet film coating is 150μm thick, with the corners thickened to 180μm. (III) Drying and Curing Curing was performed using an infrared tunnel oven with hot air at 60℃ for 30 minutes, with a set wind speed of 8m / s and an air exchange rate of 20 times / hour; the conveyor belt speed was 1.2m / min; after grinding the edge burrs with an angle grinder, the cabinet was placed at 25℃ for 24 hours to obtain a cabinet door coated with fire-retardant paint.
8. The coating process for a fire-retardant coating for cabinet doors according to claim 7, characterized in that, The water-based epoxy sealing primer is a water-based acrylic wood sealing primer.